Ação rescisória contra decisão que viola precedente vinculante - Souza, Álvaro José Haddad de (2025)
The Civil Procedure Code establishes exceptional hypotheses for rescinding the final and unappealable court decision. Among them, the judgment that clearly violates the legal norm (art. 966, V), differing from what was planned in the previous Code, which authorized rescissory actions for violating the literal provision of law. The provision aligns with the current understanding in the sense that the legal norm is the result of the interpretation of the normative statement, with the law not being the only source of law, but also the legal precedent (= ratio decidendi). Rescissory actions are expressly authorized against judgments that clearly violate binding precedents or precedents that result in binding precedents or dominant jurisprudence. Law n. 13.146/2015 added §§5° and 6°, to article 966, of the Brazilian Civil Procedure Code, to regulate this hypothesis of admitting rescissory actions. However, there are disagreements regarding the interpretation of these provisions, which are presented and compared in this work. The topic also involves applying the statement of precedent 343/Supreme Court, questioned in doctrinal terms. Thus, this study aims to analyze rescissory actions against judgments that violate binding precedents, passing through the procedural and procedural aspects.